The Influence of Transformational Leadership, Self Efficacy and Career Development on Employee Performance with Achievement Motivation as an Intervening Variable in Female Officials In the Riau Islands Provincial Government - Yeni Ardianti; Bambang Satriawan; Nolla Puspita Dewi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze how the influence of transformational leadership, self-efficacy and career development on employee performance with achievement motivation as an intervening variable in female officials in the Riau Islands Provincial Government. The analysis used in this research is parametric and non-parametric statistics using SEM-PLS (Structural Equation Modeling-Partial Least Square). Data analysis with parametric and non-parametric statistics regarding research variables, calibration tests / pilot tests, validity and reliability, Outer model and inner model analysis, as well as discussion of the results of hypothesis testing or Path Analysis. This study uses path analysis to examine relationship patterns that reveal the effect of a variable or set of variables on other variables, both direct and indirect effects. The calculation of the path coefficient in this study was assisted by SmartPLS. The test results in this study found that Transformational Leadership and Career Development had no significant effect on the Performance of Women Officials in the Riau Islands Provincial Government, while Self Efficacy had a significant effect on the Performance of Women Officials in the Riau Islands Provincial Government, Career Development and Transformational Leadership had a significant effect on the Performance of Women Officials in the Riau Islands Provincial Government Transformational Leadership, Self Efficacy and Career Development have a significant effect on Performance with Achievement Motivation as an Intervening Variable on Women Officials in the Riau Islands Provincial Government.